2021
DOI: 10.1371/journal.pone.0257326
|View full text |Cite
|
Sign up to set email alerts
|

A low-threshold intervention to increase physical activity and reduce physical inactivity in a group of healthy elderly people in Germany: Results of the randomized controlled MOVING study

Abstract: Background Lack of physical activity (PA) and a high level of physical inactivity (PI) are associated with a higher risk for mortality and responsible for several non-communicable diseases including cardiovascular disease. Higher age is associated with a decrease of PA and an increasing level of PI. Studies have shown that interventions in the elderly have the potential to increase the amount of PA and to decrease the level of PI. However, most interventions are complex, elaborated, time- and resource-consumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Ten studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] referred to published protocols [ 79 , 80 , 81 , 82 , 83 , 84 ] or trial registry records (trial IDs reported in Table 1 ) which were consulted in these cases. Nine studies [ 69 , 70 , 73 , 76 , 77 , 78 , 85 , 86 , 87 ] were judged to be of high risk of bias and four studies [ 71 , 72 , 74 , 75 ] to have some concerns. No studies were judged to be of low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] referred to published protocols [ 79 , 80 , 81 , 82 , 83 , 84 ] or trial registry records (trial IDs reported in Table 1 ) which were consulted in these cases. Nine studies [ 69 , 70 , 73 , 76 , 77 , 78 , 85 , 86 , 87 ] were judged to be of high risk of bias and four studies [ 71 , 72 , 74 , 75 ] to have some concerns. No studies were judged to be of low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In two instances [ 88 , 89 ], the authors referred to an additional paper containing more detailed information on the respective study [ 90 , 91 ]. Of the 15 included studies, 14 studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 87 , 88 , 89 ] were published in peer-reviewed journals, 14 were written in English [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 87 , 88 , 89 ] and one [ 86 ] in German. The country of origin was Germany for 13 studies [ 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 86 , 87 , 88 ] and Belgium [ 89 ] and the UK [ 72 ] for one study each.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations